The Effect of Organizational Commitment, Moral Leadership, Work Environment, Religiusity and Love of Money Towards Fraud Intention - Kamelia Astuty (Penerbit Jurnal Indonesia, 2022)
Many factors influence a person to commit cheating. Several studies have also been conducted to examine matters regarding fraud, both the factors that influence it and the impact it causes. The purpose of this study was to prove the effect of organizational commitment, leadership morale, work environment, religiosity and love of money on fraud intention among Bank Bengkulu employees. This type of research is a quantitative study. Respondents are all Bengkulu Bank employees who work in accounting and teller departments. Data collection through online surveys with google form. The results showed that organizational commitment had a negative effect on fraud intention. This means that the higher the employee's commitment to the organization, the lower the desire to commit fraud. Leadership morale has a negative effect on fraud intention. This means that the higher the morale of the leadership, the lower the desire to commit fraud. The work environment has a negative effect on fraud intention. This means that the better the work environment, the lower the desire to commit fraud. Religiosity has a negative effect on fraud intention. This means that the more religious an employee is, the lower the desire to commit fraud. Love of money has a positive effect on fraud intention. This means that the more employees love money, the more likely they are to cheat.